Gla-Rich Protein Is a Novel Vitamin K-Dependent Protein Present in Serum That Accumulates at Sites of Pathological Calcifications - Viegas, Carla S.B. (American Society for Investigative Pathology, 2009)
Mineralization of soft tissues is an abnormal process that occurs in any body tissue and can greatly increase morbidity and mortality. Vitamin K-dependent (VKD) proteins play a crucial role in these processes; matrix Gla protein is considered one of the most relevant physiological inhibitors of soft tissue calcification know to date. Several studies have suggested that other, still unknown, VKD proteins might also be involved in soft tissue calcification pathologies. We have recently identified in sturgeon a new VKD protein, Gla-rich protein (GRP), which contains the highest ratio between number of Gla residues and size of the mature protein so far identified. Although mainly expressed in cartilaginous tissues of sturgeon, in rat GRP is present in both cartilage and bone. We now show that GRP is a circulating protein that is also expressed and accumulated in soft tissues of rats and humans, including the skin and vascular system in which, when affected by pathological calcifications, GRP accumulates at high levels at sites of mineral deposition, indicating an association with calcification processes. The high number of Gla residues and consequent mineral binding affinity properties strongly suggest that GRP may directly influence mineral formation, thereby playing a role in processes involving connective tissue mineralization.